Atypical lumbar pedicle fractures. A case report and comparative review of the literature: Bisphosphonate-related? Possible matching with diagnostic criteria of atypical fractures of the femur - Emmanouil Theodorakis; Georgios Touloupakis; Guido Antonini; Maria Gabriella Lettera; Marco Teli (Brain and Spine)
Introduction: Bisphosphonates are commonly used to prevent osteoporotic fractures. Many randomized controlled trials have proved the efficacy of bisphosphonates, showing their ability to increase bone mineral density and decrease the risk of hip and vertebral fractures. Atypical, bisphosphonate-related fractures concerning the femur have been widely described and a list of primary and secondary clinical and radiographic criteria are used in order to achieve diagnosis. Research question: To identify clinical and radiographic findings for a possible association of vertebral fractures to prolonged bisphosphonate therapy. Material and methods: In this paper we present a case of an atraumatic bilateral pedicle lumbar fracture, assuming the hypothesis of an insufficiency atypical fracture due to prolonged Alendronate therapy for osteoporosis. We highlight the various aspects for diagnosis, treatment and a review of the existing literature was carried out. Discussion and conclusion: Atypical fractures in the spine are rarely reported in the literature. Pedicle anatomy is partially similar to a long bone, described as a strong bridge between the posterior arch and the vertebral body composed of a cortical bone and a cancellous core. Stress fractures are reported as a result of an underlying bone disease, trauma, post-surgery and stress fractures. In our opinion, the criteria described for atypical femoral fractures are a useful tool to also classify these rare pedicle lesions as insufficiency, bisphosphonate-correlated fractures.